Rationale for Study of the Deep Subfascial Lymphatic Vessels During Lymphoscintigraphy for the Diagnosis of Peripheral Lymphedema. (February 2019) - Campisi, Corrado Cesare; Ryan, Melissa; Villa, Giuseppe; Di Summa, Pietro; Cherubino, Mario; Boccardo, Francesco; Campisi, Corradino
Abstract : Purpose: The current study aimed to determine the utility of including the study of deep subfascial lymphatic vessels in a 2-compartment lymphoscintigraphy for the diagnosis of lymphedema in patients with limb swelling. Lymphoscintigraphy is a valuable imaging tool for the timely diagnosis of peripheral lymphedema. However, there is a lack of standardization in its application, especially regarding which type of lymphatic vessels to examine (superficial, deep, or both). Methods: Two hundred fifty-eight patients with lymphedema underwent segmental lymphoscintigraphy. The transport index (TI) was calculated to categorize the flow of the superficial and deep vessels as normal (<10) or pathological (≥10). The scores from 248 patients (48 unilateral arm, 86 unilateral leg, 114 bilateral leg) were tested with a 3-way analysis of variance to examine the relationship between affected limb, deep or superficial pathways, and primary or secondary lymphedema. The relationship between clinical presentation and TI was also investigated. Results: In general, primary and secondary lymphedema patients had similar patterns of lymphoscintigraphic lymphatic abnormalities. Patients with unilateral clinical presentation can have bilateral TI abnormalities. The vast majority of patients (88%–98%) had either the deep subfascial vessels alone, or both the superficial and deep vessels, with a pathological TI. Conclusions: A 2-compartment lymphoscintigraphy is able to accurately detect lymphatic flow abnormalities in patients with limb swelling. Given that the vast majority of patients had deep lymphatic vessels abnormalities, inclusion of these vessels in the lymphoscintigraphic diagnostic protocol is recommended.